Creación de una cafetería dulces ideales especializada en la elaboración de productos para requerimientos especiales - Yépez Cortés, María Gabriela (2016)
This project sets out guidelines for the creation of "Dulces Ideas", an artisanal enterprise specialized in the production of traditional bakery and pastries, as well as in innovation and development of recipes for diabetics, celiac disease sufferers and kosher products for consumption of customers of Jewish descent. The business idea includes medical, nutritional and gastronomical criteria, which result in customized products, designed to meet customer needs in all aspects, giving them the option to consume products that are beneficial to their health and their personal preferences. It has been considered all aspects necessary to achieve a complete, comprehensive and viable project, able to be executed subsequently. Finally, the financial analysis performed reflects the viability of the business and the chance to run with positive short- and medium-term figures. The analysis is supported by the data calculated and produced along of the research.